Endoscopic Injections of Botulinum Toxin Type A in the Piglet Esophagus Is Safe and Feasible but Did Not Result in any Significant Structural Changes 3 Days after Injection - Rose, Morten; Clarke, Patrick; Pike, Ashton H.; Zvara, Peter; Schrøder, Henrik D.; Hejboel, Eva K.; Qvist, Niels; Ellebæk, Mark B. (European Journal of Pediatric Surgery, 2022)
Introduction Treatment for long-gap esophageal atresia (LGEA) aims at achieving primary anastomosis with minimal tension. Previous studies have shown that intramural injections with botulinum toxin type-A (BTX-A) from the adventitial side can increase the elongation of the piglet and rat esophagus before bursting, and that this effect is dose and time dependent. Our aim was to determine if endoscopic injections would be feasible, safe, and with an effect on the mechanical properties of the esophagus.Methods Twenty-two male piglets (5.15 kg) were randomized into two groups, one receiving 2 units/kg BTX-A, the other equal volume 0.9% NaCl. On day 3, the esophagus was harvested and tested in a stretch-tension machine to evaluate elongation and maximum load, followed by histological examination.Results No adverse effects to the procedure were observed. No statistically significant difference in elongation or maximum load before bursting between the treatment and placebo group was found. In histopathological analysis, inflammation and abscess formation were observed with no statistically significant difference between the two groups.Conclusion Endoscopic placement of BTX-A injections in the piglet esophagus was safe and feasible but did not result in any difference in the mechanical properties or histology of the esophagus.
Keywords: esophageal atresia; long gap esophageal atresia; botulinum toxin type-A; pigs